REPRESENTATION OF ARABIC PLURAL FORMS IN CERTAIN NAMES IN NAVOI'S POEM "SADDI ISKANDARIY" - Alimova Zarifa Vaxobovna (Western European Studies, 2024)
This article discusses the plural forms of certain nouns in Alisher Navoi's epic "Saddi Iskandariy," focusing on Arabic plural suffixes and broken plural forms. It examines the morphological characteristics of specific words, their lexical meanings, and their descriptions based on Persian-Tajik dictionaries, as well as the lexical meanings in the explanatory dictionaries of Navoi's works. The main goal of the article is to identify nouns formed by the addition of Arabic plural suffixes, some of which exhibit the Arabic broken plural form. The article explains the lexical and semantic characteristics of the Persian words mentioned.
Keywords: concept of words; plurality in nouns; Arabic plurality